The mechanism of assortative mating for educational attainment: a study of Finnish and Dutch twins and their spouses - Gonggrijp, Bodine M. A.; Silventoinen, Karri; Dolan, Conor V.; Boomsma, Dorret I.; Kaprio, Jaakko; Willemsen, Gonneke (Frontiers in Genetics, 2023)
Assortative mating describes a phenomenon in which individuals with similar phenotypic traits are more likely to mate and reproduce with each other; i.e. assortative mating occurs when individuals choose partners based on their similarity or dissimilarity in certain traits. There are various theories about its underlying mechanisms, which have different genetic consequences. We examined two possible mechanisms underlying assortative mating – phenotypic assortment and social homogamy – for educational attainment in two countries utilizing data of mono- and dizygotic twins and their spouses (1,451 Finnish and 1,616 Dutch twin-spouse pairs). The spousal correlations were .51 in Finland and .45 in the Netherlands, to which phenotypic assortment contributed .35 and .30, and social homogamy .16 and .15, respectively, indicating that both social homogamy and phenotypic assortment are important processes in spouse selection in Finland and the Netherlands. In both countries, phenotypic assortment contributes to a greater degree to the similarity of spouses than social homogamy.